THE PROCESS OF THE FORMATION OF GENDER EQUALITY IN SOCIETY (Scientific journal of the Fergana State University, 2024)
As a result of the analysis of the issue of women in connection with the development of society in the article, the importance of social unity of people, family, customs, culture, international and inter-civilizational relations necessary for living as a society, religion, labor and association with public organizations, the issue of equal rights of women and men, factors of the emergence of - data such as the calculation of the social and cultural roles of both sexes in different areas of life, as well as the imbalance of ideas about them, have been scientifically researched.